(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
Gamma-ray radiation shielding properties such as linear attenuation coefficient (m), mass attenuation coefficient (m/r), half- value thickness (HVT), tenth value thickness (TVL) and mean free path (MFP) were calculated for different types of radiation absorbing materials such as Concrete, Aluminum, Iron, Copper, Lead, Lead-glass and Tungsten. These materials are being widely used as radiation shielding materials in different areas of nuclear medicine facilities for different purposes. The XCOM and in-house developed computer program were used to calculate the above mentioned parameters for gamma-ray energies of 100 keV, 200 keV and 511 keV. The gamma-ray energy range used in nuclear medicine is between 100 keV and 511 keV. Results show that attenuation coefficient decreases with increase of gamma-ray energy, and attenuation coefficient increases with increase of density and shows significant variation for different materials. Linear attenuation coefficient depends on the energy of incident gamma-rays and the nature of the absorbing materials. These gamma-ray attenuation parameters of different absorbing materials can be used for proper shielding design of syringe shield, isotope storage container, isotope transport container, personnel protective shield barrier, radioactive waste storage facility etc. in nuclear medicine services. Bangladesh J. Nuclear Med. 21(2): 108-114, July 2018